Strategi Peningkatan Pelayanan Departemen Fresh Food Tiara Dewata Menggunakan Metode Quality Function Deployment (QFD) - Candigo, Tissa Meiya; Hartiati, Amna; Yuarini, Dewa Ayu Anom (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2022)
Consumer complaints indicate that there are still shortcomings in the service of the Tiara Dewata fresh food department. This is a reference for Tiara Dewata to analyze these problems to maintain consumers trust. This study aims to help analyze the needs and desires of consumers and find out the right strategies for improving the services of the Tiara Dewata fresh food department. The research was conducted through a survei of 100 consumers and interviews with Tiara Dewata, Denpasar. Based on the QFD analysis, there are 11 attributes of pelanggan interest and 14 technical parameters to achieve satisfaction of pelanggan interest attributes. The results of the analysis show that the company can still improve services with the highest improvement ratio with a value of 1.39, namely the completeness of the product pricetag (X4) and the employee's understanding of the product (X6). In addition, the company can improve the technical response to complaints to consumers so that consumers satisfaction and company targets can be achieved optimally.